Information vs. knowledge: A case study of knowledge management - Murugesan, R.; Sriraam, N. (2004)
Knowledge has widely been acknowledged as one of the most important factors for corporate competitiveness, and have witnessed an explosion of IS/IT solutions claiming to provide support for knowledge management (KM).A relevant question to ask, though, is how systems and technology intended for information such as the intranet can be able to assist in the managing of knowledge.To understand this, we must examine the relationship between information and knowledge.Building on Polanyi’s theories, all knowledge is tacit, and what can be articulated and made tangible outside the human mind is merely information.However, information and knowledge affect one another. By adopting a multi-perspective of the intranet where information, awareness, and communication are all considered, this interaction can best be supported and the intranet can become a useful and people inclusive KM environment.In this paper, seven enabling factors of organizational creativity are identified and discussed. These factors are then compared to the specific characteristics of intranet technology in order to find out when and how this environment may stimulate creativity